SMART TEACHING WITH CANVA: OPTIMALISASI KNOWLEDGE SHARING UNTUK PENGUATAN KOMPETENSI DIGITAL DOSEN MANAJEMEN - Latupapua, Conchita V; Leuhery, Ferdy; Rehatta, Pieter N. R; Chandra, Felix; Noya, Ryalno Stefano (Jurnal Kreativitas dan Inovasi (Jurnal Kreanova), 2025)
This Community Service (PKM) activity, titled Smart Teaching with Canva: Optimizing Knowledge Sharing to Strengthen the Digital Competence of Management Lecturers, aims to enhance lecturers’ ability to creatively and effectively integrate digital technology into the teaching and learning process. Through the implementation of the smart teaching approach combined with knowledge sharing practices, this program seeks to strengthen pedagogical and digital competencies, enabling lecturers to become more adaptive to the rapid evolution of educational technology. The objects of this PKM are lecturers from the Management Department, Faculty of Economics and Business, Pattimura University, consisting of five permanent lecturers and two student assistants who served as technical facilitators. The activities were carried out through intensive workshops and interactive training sessions on using Canva to design digital teaching media such as interactive videos, presentations, infographics, and academic promotional materials. The results indicated significant improvements in participants’ digital literacy, visual creativity, and collaborative knowledge-sharing skills. Furthermore, this program contributed to fostering a culture of innovation, collaboration, and continuous learning within the academic community, aligning with the broader digital transformation of higher education.